2009
DOI: 10.1111/j.1523-1739.2008.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Generality of Models that Predict the Distribution of Species: Conservation Activity and Reduction of Model Transferability for a Threatened Bustard

Abstract: Predictive models can help clarify the distribution of poorly known species but should display strong transferability when applied to independent data. Nevertheless, model transferability for threatened tropical species is poorly studied. We built models predicting the incidence of the critically endangered Bengal Florican (Houbaropsis bengalensis) within the Tonle Sap (TLS) floodplain, Cambodia. Separate models were constructed with soil, land-use, and landscape data and species incidence sampled over the ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 14 publications
0
26
0
3
Order By: Relevance
“…Implications of the novel combined approach for nature conservation Predictive models have been used in a wide array of applications directed at evaluating and planning the conservation of valuable elements of biodiversity and ecosystems (Pearce and Ferrier 2001;Muñoz et al 2005;Gray et al 2008), as well as for forecasting their responses to environmental changes (Guisan and Theurillat 2000;Araújo et al 2005;Broennimann et al 2006). The more informative character of the combined models compared to the non-combined, traditional models, can make them particularly valuable for multiple applications in fields related to conservation, management and monitoring.…”
Section: No Change Colonisation Extinctionmentioning
confidence: 99%
“…Implications of the novel combined approach for nature conservation Predictive models have been used in a wide array of applications directed at evaluating and planning the conservation of valuable elements of biodiversity and ecosystems (Pearce and Ferrier 2001;Muñoz et al 2005;Gray et al 2008), as well as for forecasting their responses to environmental changes (Guisan and Theurillat 2000;Araújo et al 2005;Broennimann et al 2006). The more informative character of the combined models compared to the non-combined, traditional models, can make them particularly valuable for multiple applications in fields related to conservation, management and monitoring.…”
Section: No Change Colonisation Extinctionmentioning
confidence: 99%
“…Published studies with the required information for our analysis were only available for selected animal species, including a limited number of fishes (Lamberts 2001;Lim et al 1999), water snakes (Brooks et al 2009), Bengal florican (Gray et al 2009), grey-headed fisheagle (Tingay et al 2010), aquatic invertebrates (Tanaka & Ohtaka 2009), and zooplankton/zoobenthos (Ohtaka et al 2010). Data for other species were inferred by synthesizing Tonle Sap biodiversity data with generally available lifehistory characteristics (Bonheur & Lane 2002;Campbell et al 2006;Davidson 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Some fish species of the Tonle Sap are reliant on the nutrient-rich habitats made available during the flood pulse aquatic phase to complete their life-cycles; others require the refugial ponds created by the inundation of the habitat to survive the dry season. Various endangered bird species inhabit the Tonle Sap, most of which have particular habitat preferences; for example, the greyheaded fish-eagle (Ichthyophaga ichthyaetus) is typically found in forested areas (Tingay et al 2010), whereas the Bengal florican (Houbaropsis bengalensis) is predominantly found in grasslands (Gray et al 2009). The close linkage of these species to their habitats and the restrictions that this imposes suggests that flooding and annual cyclical changes of habitats in the Tonle Sap are crucial for maintaining biological productivity and biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Peterson 2003Peterson , 2006Sutherst 2003), others have suggested that models will not be able to predict the full extent of invasions when species adapt or evolve to cope with new conditions or face a new suite of interacting species (Broennimann et al 2007;Broennimann and Guisan 2008). Indeed, there is increasing evidence that models cannot always be transferred to new geographic locations (Gray et al 2009;Randin et al 2006;Zanini et al 2009). …”
Section: Introductionmentioning
confidence: 99%